28-4n=-4n-7(n+3)

Simple and best practice solution for 28-4n=-4n-7(n+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 28-4n=-4n-7(n+3) equation:


Simplifying
28 + -4n = -4n + -7(n + 3)

Reorder the terms:
28 + -4n = -4n + -7(3 + n)
28 + -4n = -4n + (3 * -7 + n * -7)
28 + -4n = -4n + (-21 + -7n)

Reorder the terms:
28 + -4n = -21 + -4n + -7n

Combine like terms: -4n + -7n = -11n
28 + -4n = -21 + -11n

Solving
28 + -4n = -21 + -11n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '11n' to each side of the equation.
28 + -4n + 11n = -21 + -11n + 11n

Combine like terms: -4n + 11n = 7n
28 + 7n = -21 + -11n + 11n

Combine like terms: -11n + 11n = 0
28 + 7n = -21 + 0
28 + 7n = -21

Add '-28' to each side of the equation.
28 + -28 + 7n = -21 + -28

Combine like terms: 28 + -28 = 0
0 + 7n = -21 + -28
7n = -21 + -28

Combine like terms: -21 + -28 = -49
7n = -49

Divide each side by '7'.
n = -7

Simplifying
n = -7

See similar equations:

| (2x-1)(3x-1)=(x+1)(4x-2) | | 8x-18=39x+19 | | logx-1(4x-4)=2 | | t^2+13t=0 | | 4e^3x-2=244 | | 7(n+6)=98 | | 2(6x-7)=-39+7x | | 105=-7(x-8) | | -9-4x=-6x-19 | | 0.8x-1.8=3.9x+1.9 | | 6(1-4m)=-90 | | 5(2+2x)=4(3-3x) | | (4n-7)(8n-7)= | | 17=1+4p | | cos(3x+20)=0.2 | | 240=12x | | ab=9 | | 1=4+p | | 8x^2-12y+4=y+10 | | cos(3o+20)=0.2 | | 4+3x+6=4x-5 | | x+(-10)=-22 | | 27-7r=-(1+3r) | | 20+2p=8+6(-8+2p) | | -5(a+6)=-14-7a | | 2y^2+14=104 | | x(5)=-5-1 | | 2(x+6)=3(x+4)+5 | | 180(n-1)=900 | | -84=7(p-4) | | -105=-7(1-2r) | | -75-18v=-70 |

Equations solver categories